Identification of Lactic Acid Bacteria From Pineapple Peels Fermented Beverages Through 16S rRNA Gene Analysis - Ariwidiani, Ni Nyoman Nyoman; Pauzan, Pauzan; Wahdaniyah, Rabiyatun; Mahavira Diputra, I Ketut (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2026)
Stunting is associated with intestinal microbiota dysbiosis, which disrupts bodily functions and contributes to stunted growth in children. Consuming probiotics is an alternative way to prevent gastrointestinal infections caused by dysbiotic microbiota. Probiotics work by balancing the composition of the intestinal microbiota and stimulating the immune response. The use of fermented products is well known; one example is tepache, a fermented pineapple peel drink containing lactic acid bacteria with potential as a probiotic. This study aims to identify lactic acid bacteria from fermented pineapple peel drinks with potential as probiotics for intestinal microbiota health. Pineapple peel fermentation was carried out for 3 days; the resulting fermentation liquid was cultured on MRS agar and tested for characteristics using biochemical tests. Identification of isolates from the pineapple peel fermentation culture was performed by sequencing the 16S rRNA gene. The results of the isolate culture showed growth of 2 bacterial isolates with characteristics consistent with LAB colonies. Microscopic tests showed that isolate N1 was a gram-positive, rod-shaped LAB, and isolate N2 was a gram-positive, cocobacilli-shaped LAB. Identification of the 16S rRNA gene from isolate N1 showed characteristics similar to Lactiplantibacillus plantarum, while isolate N2 showed characteristics similar to Leuconostoc mesenteroides. These isolates are common lactic acid bacteria found in fermented foods and may be potential probiotic candidates, but functional and safety evaluations are needed to confirm their probiotic properties.